Financial Literacy Through Financial Reporting Training for MSMEs In Tugu Village - Rahayu, Puji; Harianto, Kukuh (Universitas Putra Indonesia YPTK Padang, 2025)
MSMEs a crucial role in the local economy in Tugu Village, Sendang District, Tulungagung Regency, East Java Province. Tugu Village is a tourism village center that upholds local wisdom in Tulungagung Regency. However, the majority of MSMEs in this region face serious challenges in financial management, particularly the inability to prepare financial reports according to MSME standards. This leaves them unaware of their business's profit or loss status due to a lack of supporting records and even administrative difficulties when borrowing capital from banks. This community service activity aims to provide education and training on preparing financial reports in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities. The implementation method involved interactive lectures and demonstrations for 25 MSME participants. The results showed a significant increase in participant understanding, with 80% of participants finding the activity very beneficial and successfully preparing a profit and loss report after the training session. This education is expected to help MSMEs achieve financial transparency and facilitate access to capital from formal financial institutions in the future